PROMOTING BULELENG TOURISM THROUGH LOVINA FESTIVAL - Putu Ratna Juwita Sari (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2017)
Tourism in the district of Buleleng, North Bali, is in a process of development so that it is expected to be able produce products of tourism as rapidly developing as the South Bali. The government of Buleleng district has launched an intensive campaign with an aim to develop object of tourism and also holding festivals expected to be able to attract tourist to come. One of the festival is the Lovina Festival which aims to promote the tourism of Buleleng District to improve the economy of Buleleng citizen and increasing the locally-generated revenue. The objective of this research is to learn the precise and effective promotion to implement to attract the interest of tourist to spend their vacation in Buleleng regency especially on the Lovina region. The research method which will be used in this research is the method of qualitative using data gathering technique, observation, interviews and documentation. The result of this research shows the inadequacy of promotional media in use, which resulted in less enthusiasm from visiting tourists.